Geschiebekundlich-stratigraphische Untersuchungen in der südlichen Lüneburger Heide - Meyer, Klaus-Dieter (Hannover : Universität Hannover. Institut für Geologie und Paläontologie, 1998)
An outline of the Pleistocene history of the southern Lüneburg Heide is given based on the interpretation of exposed sections and indicator-stone analysis. Locally, Elsterian sediments crop out at the surface, mainly near the Holsteinian kieselgur (diatomite), thus indicating the existence of a pre-Saalian relief. Most of the Pleistocene deposits were formed during the three Saali- an ice advances. The ground moraine (basal till) of the first advance (the main Drenthe moraine) and its outwash sands are only locally exposed and only at the margin of the Aller valley do they form a relatively extensive plain. To the north, they are overlain by outwash sands of the late Drenthe advance. Also the Uelzen end moraine consists mainly of these outwash sands. The Uelzen moraine was overridden by the same ice advance. The Warthe ice sheet left only minor traces ridge; its advance came to a final stop at the already dumped morainic material. : Mittels Aufschlußinterpretationen und Leitgeschiebeanalysen wird ein Abriß der pleistozänen Geschichte der südlichen Lüneburger Heide gegeben. Elsterzeitliche Sedimente kommen lokal an die Oberfläche, hauptsächlich in der Nähe der holsteinzeitlichen Kieselgur, damit ein prä-saalezeitliches Relief andeutend. Die Hauptmenge der pleistozänen Sedimente ist während der drei saalezeitlichen Eisvorstöße gebildet worden. Die Grundmoräne des ersten Vorstoßes (Dren- the-Hauptmoräne) und deren Vorschüttsande waren nur lokal aufgeschlossen und treten erst am Allertalrand flächenhaft zutage. Sie werden nach Norden zu von Schmelzwassersanden des Jüngeren Drenthe-Vorstoßes überlagert, die auch hauptsächlich die Uelzener Endmoräne aufbauen, welche vom gleichen Vorstoß überfahren wurde. Das Warthe-Eis hat an diesem Höhenrücken nur geringe Spuren hinterlassen, es fand an dem bereits bestehenden Wall sein Ende.